THE BENEFITS OF STORIES IN MAMANDA AS THE FORMATION OF MILENIAL GENERATION CHARACTERS - Dewi, Dwi Wahyu Candra; Nuryatin, Agus; Supriyanto, Teguh; Zulaeha, Ida (International Journal of Psychosocial Rehabilitation, 2020)
One of the traditional literature in Banjarmasin, South Kalimantan is mamanda. Mamanda’s story is a literary work that was born from poetry and saga books. Mamanda’s story was also adapted from the surrounding environment as a form of social criticism related to matters in the community. Mamanda stories are displayed in the mamanda performance art and its existence depends on the existence of mamanda performances. Concerns about the Mamamanda story began to emerge when millennials preferred works from abroad. They think that regional works are less popular. The development of the times has shifted literary works such as Mamanda’s story to less attention. The study was conducted to obtain the usefulness of Mamanda stories in the formation of millennial generation characters. The study was conducted by dialectical method and using an interdisciplinary qualitative research approach. Utilization in Mamanda stories in the form of educational values. The use of the Mamanda story in the form of educational value is an effort to prevent the negative impacts of the times. Based on research, the usefulness of Mamanda’s story can shape the character of politeness, harmony, and cooperation.